2021
DOI: 10.1042/bcj20200937
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the LRRK code: LRRK1 and LRRK2 phosphorylate distinct Rab proteins and are regulated by diverse mechanisms

Abstract: Autosomal dominant mutations in LRRK2 that enhance kinase activity cause Parkinson’s disease. LRRK2 phosphorylates a subset of Rab GTPases including Rab8A and Rab10 within its effector binding motif. Here, we explore whether LRRK1, a less studied homologue of LRRK2 that regulates growth factor receptor trafficking and osteoclast biology might also phosphorylate Rab proteins. Using mass spectrometry, we found that in LRRK1 knock-out cells, phosphorylation of Rab7A at Ser72 was most impacted. This residue lies a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 69 publications
1
55
0
Order By: Relevance
“…Additionally, we show that MLi-2 at a concentration of up to 300 nM does not result in dephosphorylation of Rab7a, the endogenous phosphorylation substrate of the only known LRRK2 homologue LRRK1 [25] or dephosphorylation of AMPK at threonine 172. Serine 935 dephosphorylation of LRRK2 is seen at maximal levels starting at 100 nM MLi-2 and above.…”
Section: Measured Ratio (L/h) Expected Ratio (L/h)mentioning
confidence: 81%
See 3 more Smart Citations
“…Additionally, we show that MLi-2 at a concentration of up to 300 nM does not result in dephosphorylation of Rab7a, the endogenous phosphorylation substrate of the only known LRRK2 homologue LRRK1 [25] or dephosphorylation of AMPK at threonine 172. Serine 935 dephosphorylation of LRRK2 is seen at maximal levels starting at 100 nM MLi-2 and above.…”
Section: Measured Ratio (L/h) Expected Ratio (L/h)mentioning
confidence: 81%
“…The MJFF-total Rab10 mouse antibody was from nanoTools (Cat# 0680–100/Rab10-605B11). Rabbit monoclonal antibodies for total LRRK2 (N-terminus, residues 100–500, UDD3) and phospho-Ser935 LRRK2 (UDD2) as well as the sheep polyclonal antibodies for LRRK1 (sheep number S405C, 2nd bleed) were expressed and purified at the University of Dundee as described previously [ 7 , 10 , 25 ] and are available from MRC PPU Reagents and Services ( https://mrcppureagents.dundee.ac.uk/ ). The sheep polyclonal PPM1H antibodies against the full length PPM1H protein have been described before [ 2 ] and are also available from MRC PPU Reagents and Services (sheep number DA018, https://mrcppureagents.dundee.ac.uk/ ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes play a crucial role during immune response and several studies have linked LRRK2 signaling to inflammation in general and neuroinflammation specifically (reviewed in [25]. Interestingly, recently, it was shown that LRRK1, the human homolog of LRRK2, phosphorylates a different subset of Rab proteins than LRRK2, suggesting that LRRK enzymes are Rab specific kinases [26].…”
Section: Lrrk2: Structure Function and Role In Pdmentioning
confidence: 99%